Heterogeneous Causal Effects of Financial Incentives on Weight Loss – Results of a Large Prospective Randomized Trial - Monika Reuss-Borst; Alfredo R. Paloyo; Arndt R. Reichert; Harald Tauchmann (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2012)
In a randomized controlled trial involving 700 obese persons assigned to three experimental groups, we test whether financial incentives have heterogeneous effects on weight reduction. While two treatment groups obtain EUR 150 and EUR 300, respectively, for achieving an individually-assigned target weight within four months, a control group receives no such premium. The objective is to identify subgroups of patients (male/female, natives/migrants, etc.) who respond more than others to financial incentives. Our conclusions are the following: (1) monetary rewards effectively induce obese individuals to reduce weight across all subgroups; (2) the magnitude of the reward is relevant only for certain subgroups; (3) for people who do not lose weight via conventional weight-loss intervention programs, financial incentives are an effective supplement to induce weight loss. – – Im Rahmen eines randomisierten Experiments mit 700 adipösen Studienteilnehmern und drei Experimentalgruppen wird untersucht, ob die Effektivität von finanziellen Anreizen zur Gewichtsreduktion von bestimmten individuellen Merkmalen abhängt. Während zwei Gruppen bis zu 150 Euro und 300 Euro für das Erreichen eines individuellen Zielgewichts versprochen wurde, war eine Kontrollgruppe keinem finanziellen Anreiz ausgesetzt. Zentrales Studienziel ist die Identifizierung von Patientensubgruppen (Männer/Frauen, Migranten/Nicht-Migranten, etc.), die stärker auf finanzielle Anreize wirken als andere. Unsere Analyse kommt zu folgendem Ergebnis: (1) finanzielle Anreize regen alle betrachtete Subgruppen zur Gewichtsreduktion an, (2) die Höhe der Prämie ist nur für bestimmte Subgruppen relevant und (3) Geldprämien stellen eine effektive Ergänzung zu Standardbehandlungsprogrammen auch bei denjenigen Adipösen dar, die alleine auf Basis der Standardbehandlung keine nennenswerte Abnehmerfolge erzielen können.
Keywords: I10; I18; H23; C93; 330; randomized experiment; financial incentives for weight loss; obesity; subgroups; effect heterogeneity